SPE Asia Pacific Oil &Amp; Gas Conference and Exhibition 2006
DOI: 10.2118/100880-ms
|View full text |Cite
|
Sign up to set email alerts
|

Smart Snake Wells in Champion West—Expected and Unexpected Benefits From Smart Completions

Abstract: Snake wells are laterally weaving ("snaking") extended reach horizontal wells that drain a number of vertically stacked, structurally dipping reservoirs. This creates multiple drainage points in each sand and effectively achieves a similar drainage pattern to a multilateral well at a fraction of the cost and technical complexity. The wells are completed with multiple hydraulically controlled interval control valves (ICV) and external casing packers or swellable packers. In addition, the completion includes per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Previously these types of model-based optimization strategies (proactive strategies) were presented in several publications (refer, for instance, (Yeten et al, 2004;Obendrauf et al, 2006;Emerick and Portella, 2007;Chen et al, 2009;van Essen et al, 2010;Su and Oliver, 2010) and showed good results. We do believe that it is difficult and inefficient to implement the aforementioned approaches in full field reservoir models directly, because they would result in large, multidimensional and timeconsuming optimization problems.…”
Section: Framework For Modeling and Optimizationmentioning
confidence: 99%
“…Previously these types of model-based optimization strategies (proactive strategies) were presented in several publications (refer, for instance, (Yeten et al, 2004;Obendrauf et al, 2006;Emerick and Portella, 2007;Chen et al, 2009;van Essen et al, 2010;Su and Oliver, 2010) and showed good results. We do believe that it is difficult and inefficient to implement the aforementioned approaches in full field reservoir models directly, because they would result in large, multidimensional and timeconsuming optimization problems.…”
Section: Framework For Modeling and Optimizationmentioning
confidence: 99%